Quality of Work Life AND Job Satisfaction of Nursery Workers in Related and Unrelated Workplaces in Saudi Arabia - Ghufran Abdulrazaq Alhmood et al. (International Journal of Scientific Research and Innovative Studies, 2024)
The quality of work life (QWL) and job satisfaction are critical factors in determining employee performance, well-being, and retention, especially in the field of nursery care, where the physical and emotional demands are high. This review focuses on the QWL and job satisfaction of nursery workers in Saudi Arabia, comparing those working in related (childcare and educational settings) and unrelated workplaces. By exploring the factors influencing QWL and job satisfaction, the review aims to provide insights into the challenges and rewards of nursery work in different settings within Saudi Arabia, ultimately contributing to workforce management and policy improvements. Keywords: Quality of Work Life, Job Satisfaction of Nursery Workers, Related and Unrelated Workplaces. Received Date: September 14, 2024 Accepted Date: October 12, 2024 Published Date: November 13, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/223